Analyzing the role of gender in entrepreneurship education and economic success in developing nations: the case of Colombia - Mario Alberto de la Puente Pacheco; Jose Torres; Julio Cesar Cantillo Padron; Maria Claudia Pacheco Barros; Heidy Rico (Cogent Economics & Finance)
This study examines the role of gender in entrepreneurship education and its influence on business success in the city of Barranquilla, Colombia. The research question focuses on gender-specific patterns of participation in entrepreneurship education programs and the impact on business growth. Two hypotheses are tested to explore differences in program access between men and women and the relationship between education participation and business success for both genders. Data from 89 participants were analyzed using chi-square tests, t-tests, and regression analysis. The findings suggest gender-specific differences in program access and a positive relationship between education participation and business success, with varying effects based on gender. The study highlights the importance of promoting gender diversity in entrepreneurship education to foster an inclusive and supportive entrepreneurial ecosystem in Barranquilla.